Re-ranking regular seasons in the National Basketball Association's modern era : A replication and extension of Pradhan (2018). Issue 7 (3rd October 2021) - Pradhan, Sean; Chachad, Ravi
Abstract: The present study serves as a replication and extension of previous work by Pradhan (2018), which effectively ranked the top-100 seasons in the National Basketball Association's (NBA) Modern Era using grey relational analysis (GRA), with player efficiency rating (PER) as a reference point. The current investigation utilizes data from 1, 843 unique players comprising 9, 726 regular seasons in an attempt to both replicate the original study and provide other considerations for ranking the performance of professional basketball players. Regular season data using the identical performance criteria as Pradhan (2018) were examined using two forms of multi-criteria decision-making (MCDM) analysis: GRA and technique for order of preference by similarity to ideal solution (TOPSIS). Results from the current study offer a successful replication of Pradhan (2018), along with alternative considerations for ranking regular season performance in the NBA. Limitations of this work and directions for continued research in this realm are also discussed.